1999
DOI: 10.1159/000007997
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Nitrate Levels in Patients with Multiple Sclerosis

Abstract: It has been suggested that nitric oxide (NO) could be implicated in the pathogenesis of multiple sclerosis (MS). Recently, two groups reported increased cerebrospinal fluid (CSF) nitrate levels (oxidation product that provides an indirect estimation of NO) in MS patients. However, another group did not confirm these findings. We studied the CSF and plasma levels of nitrate with a kinetic cadmium reduction method in 11 MS patients and 25 matched controls. The CSF nitrate levels and the CSF/plasma nitrate ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
(26 reference statements)
2
9
1
Order By: Relevance
“…As the blood arginine level and nitrogen in the diet may affect NO 2 -/NO 3 -levels, CSF analysis of NO is reported to be a more re liable index [29]. Studies reporting increased CSF NOx (nitrite + nitrate) levels and decreased serum NO 2 -/NO 3 -levels [5] support our findings. However, contrary to our data; plasma and CSF nitrite and nitrate levels were observed to be elevated in MS in the studies conducted by C Larlori et al [10] and Miller et al [18].…”
Section: Discussionsupporting
confidence: 86%
“…As the blood arginine level and nitrogen in the diet may affect NO 2 -/NO 3 -levels, CSF analysis of NO is reported to be a more re liable index [29]. Studies reporting increased CSF NOx (nitrite + nitrate) levels and decreased serum NO 2 -/NO 3 -levels [5] support our findings. However, contrary to our data; plasma and CSF nitrite and nitrate levels were observed to be elevated in MS in the studies conducted by C Larlori et al [10] and Miller et al [18].…”
Section: Discussionsupporting
confidence: 86%
“…However, de Bustos and colleagues [5] did not find any difference in CSF nitrate concentrations between control subjects and MS patients. Furthermore, serum nitrate concentrations were found to be lower than normal controls.…”
Section: Discussionmentioning
confidence: 85%
“…However, it has been reported that high amounts of NO have antiproliferative and/or cytotoxic effects in rat oligodendrocyte cultures leading to damage [4]. Also, in an experimental model the inhibition of inducible nitric oxide synthase (iNOS) expression and NO production prevented development of allergic encephalomyelitis [5]. These reports indicate the neurotoxicity of excessive amounts of NO in MS [22].…”
Section: Introductionmentioning
confidence: 99%
“…Most noteworthy is Tavazzi et al's study [16] of a large cohort of 113 RRMS patients in whom serum tNOx levels were significantly higher (p<0.001) in RRMS patients than in health controls. Three studies described no significant difference but were heterogeneous as to the MS disease phenotype, and none considered patients following an acute relapse [24][25][26]. A single study [27] found the opposite: significantly lower mean tNOx in RRMS patients compared to control groups; no significant study characteristics were identified to explain this disparity.…”
Section: Peripheral Bloodmentioning
confidence: 99%
“…In one study, mean CSF tNOx was significantly higher in RRMS than SPMS groups [33], supporting a role for tNOx as a marker of inflammatory disease activity. Two studies described no significant difference in CSF tNOx between MS and control groups but neither offered details on the disease activity of their patient populations [24,26]; case-mix differences may account for the disparity in the outcomes of these studies. Overall, there is good evidence for tNOx as a diagnostic marker in MS, particularly in acute MS relapse.…”
Section: Csfmentioning
confidence: 99%